"Analisis Trend Kinerja Keuangan pada PT Sri Rejeki Isman Tbk " Tahun 2013-2019 - Asep Sunandar, (Manajemen Kreatif Jurnal, 2025)
This study aims to determine and describe the financial performance of PT Sri Rejeki Isman Tbk from 2013 until 2019. The method used in this study was quantitative descriptive analysis using profitability ratio measurements which were then concluded by trend analysis. The data used in this study was secondary data with documentation studies obtained from the Indonesia Stock Exchange in the form of company financial statements from 2013 until 2019.The results of this study indicated that Net Profit Margin had a positive trend, so that the financial performance in the research year was in a good condition. Return on Assets had a negative trend, so that the financial performance in the year of the study was in an unfavorable condition. Return on Equity had a negative trend, so that the financial performance in the research year was not in a good condition